Plasma and urine pharmacokinetics of two formulations of dexamethasone in greyhound dogs. Issue 5 (17th March 2021) - Morris, Tim; Paine, Stuart W.; Zahra, Paul; Li, Eric; Colgan, Sally; Karamatic, Steven
Abstract: Dexamethasone, formulated as sodium phosphate and as phenylpropionate combined with sodium phosphate, was administered subcutaneously to six greyhounds. Plasma and urine were collected for up to 240 h and analysed with a limit of quantification (LOQ) of at least 100 pg/ml for dexamethasone. Dexamethasone, formulated as sodium phosphate, terminal half‐life was 10.4 h in plasma and approximately 16 h in urine, and at 96 h, plasma hydrocortisone concentrations returned to background with dexamethasone levels around the LOQ. Dexamethasone, formulated as phenylpropionate combined with sodium phosphate, terminal half‐life, was 25.6 h in plasma and approximately 26 h in urine, and at 96 h, plasma hydrocortisone concentrations returned to background with dexamethasone levels in three of the six greyhounds around the LOQ. Critical assessment of the pharmacokinetic and pharmacodynamic data indicated how it might be utilized for medication control in racing greyhounds.